2021
DOI: 10.3390/antiox10111771
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Chemical Profiles and Biological Values of Two Spondias Species (S. dulcis and S. mombin): Valuable Sources of Bioactive Natural Products

Abstract: Spondias species have been used in traditional medicine for different human ailments. In this study, the effect of different solvents (ethyl acetate, methanol, and water) and extraction methods (infusion, maceration, and Soxhlet extraction) on the enzyme inhibitory activity against acetylcholinesterase, butyrylcholinesterase, tyrosinase, α-amylase, α-glucosidase, and antioxidant properties of S. mombin and S. dulcis leaves and stem bark were evaluated. Ultra-high-performance liquid chromatography–high resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…Elufioye et al (2017) further stated that SM leaves can be chewed with Cola acuminata seeds to enhance the memory and anti‐aging abilities of the plant. Furthermore, SM leaves are crushed along with lemon and used orally as anthelminthic agents (Sinan et al, 2021). Meanwhile, Sinan et al (2021) attributed the medicinal properties of the plant to its secondary metabolites (such as flavanonols, gallic acids derivatives, tannins, flavanones, and flavanols).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elufioye et al (2017) further stated that SM leaves can be chewed with Cola acuminata seeds to enhance the memory and anti‐aging abilities of the plant. Furthermore, SM leaves are crushed along with lemon and used orally as anthelminthic agents (Sinan et al, 2021). Meanwhile, Sinan et al (2021) attributed the medicinal properties of the plant to its secondary metabolites (such as flavanonols, gallic acids derivatives, tannins, flavanones, and flavanols).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SM leaves are crushed along with lemon and used orally as anthelminthic agents (Sinan et al, 2021). Meanwhile, Sinan et al (2021) attributed the medicinal properties of the plant to its secondary metabolites (such as flavanonols, gallic acids derivatives, tannins, flavanones, and flavanols). The neuroprotective properties of SM methanol (50, 100, and 150 mg/kg bwt) and flavonoid‐rich (25, 50, and 75 mg/kg bwt) leave extracts against cyanide‐induced neurotoxicity in rats has also been studied and it was concluded that SM extracts offered neuroprotective effects with flavonoids implicated as the probable constituent eliciting the neuroprotective effects (Akinmoladun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of O -glycosides, including 2′-hydroxyflavone, 7,4′-dihydroxyflavone, apigenin, luteolin, kaempferol, quercetin, myricetin, and acacetin derivatives were identified or tentatively annotated in the studied extracts. Hexosyl, deohyhexosyl, pentosyl, and acetylhexosyl moieties were witnessed by the neutral losses of 162.053, 146.058, 132.042, and 204.064 Da, respectively [ 43 , 44 ]. Compound 32 gave a fragment ion at m / z 415.103 and a base peak at m / z 253.050, corresponding to the consecutive losses of ethyl maleic acid and hexose ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 32 was related to 7,4 -dihydroxyflavone O-hexoside-O-ethylmaleate (Table 2). In addition, seven diglycosides (33)(34)(35)(36)(37)(38)(39) and four triglycosides (40)(41)(42)(43) were tentatively identified in the studied Primula extracts (Table 2). Compounds 6,9,11,12,13,16,17,22,24,26,30,31,33,35,37,and 38 were identified by comparison with authentic standards.…”
Section: Flavones and Flavonolsmentioning
confidence: 98%
“…Other studies have shown the presence of important bioactive compounds in Spondias sp. such as ellagic acid [ 6 ], gallic acid, catechin, chlorogenic acid, caffeic acid [ 26 ], and isoquercetin [ 27 ], though these are in lower concentrations.…”
Section: Bioactive Compoundsmentioning
confidence: 99%